Unveiling the nature of infrared bright, optically dark galaxies with early JWST data. Issue 1 (29th March 2023) - Barrufet, L; Oesch, P A; Weibel, A; Brammer, G; Bezanson, R; Bouwens, R; Fudamoto, Y; Gonzalez, V; Gottumukkala, R; Illingworth, G; Heintz, K E; Holden, B; et al.
ABSTRACT: Over the last few years, both Atacama Large Millimeter/submillimeter Array (ALMA) and Spitzer observations have revealed a population of likely massive galaxies at z > 3 that was too faint to be detected in Hubble Space Telescope ( HST ) rest-frame ultraviolet imaging. However, due to the very limited photometry for individual galaxies, the true nature of these so-called HST -dark galaxies has remained elusive. Here, we present the first sample of such galaxies observed with very deep, high-resolution NIRCam imaging from the Early Release Science programme CEERS. 30 HST -dark sources are selected based on their red colours across 1.6–4.4 $μ$ m. Their physical properties are derived from 12-band multiwavelength photometry, including ancillary HST imaging. We find that these galaxies are generally heavily dust-obscured ( AV ∼ 2 mag), massive (log ( M /M⊙ ) ∼ 10), star-forming sources at z ∼ 2−8 with an observed surface density of ∼0.8 arcmin −2 . This suggests that an important fraction of massive galaxies may have been missing from our cosmic census at z > 3 all the way into the Epoch of Reionization. The HST -dark sources lie on the main sequence of galaxies and add an obscured star formation rate density of $\mathrm{3.2^{+1.8}_{-1.3} × 10^{-3} \, {\rm M}_{\odot }\, yr^{-1}\, Mpc^{-3}}$ at z ∼ 7, showing likely presence of dust in the Epoch of Reionization. Our analysis shows the unique power of JWST to reveal this previously missing galaxy population and to provide a more complete census of galaxies at z = 2−8 based on rest-frame optical imaging.